Impact of the Replacement of a Triphenylamine by a Diphenylmethylamine Unit on the Electrochemical Behavior of Pentaerythritol‐Based Push‐Pull Tetramers. Issue 16 (5th July 2019) - Malacrida, Claudia; Habibi, Amir Hossein; Gámez‐Valenzuela, Sergio; Lenko, Illia; Marqués, Pablo Simón; Labrunie, Antoine; Grolleau, Jérémie; López Navarrete, Juan T.; Ruiz Delgado, M. Carmen; Cabanetos, Clément; Blanchard, Philippe; Ludwigs, Sabine
Abstract: The synthesis of a tetra‐functionalized pentaerythritol core decorated with N ‐methyl‐ N, N ‐diphenylamine‐based push‐pull chromophores and its electropolymerization to 3D push‐pull networks are described. The electrochemical and absorption behaviors of the tetramer are compared with the one of two reference linear push‐pull compounds, carrying triphenylamine (TPA) or methyldiphenylamine (MeDPA) donor groups, a thienyl linker and a dicyanovinyl acceptor group (DCV). We found that substituting the outer phenyl with a methyl group causes important differences in the radical cation stability, such that MeDPA chromophore generates stable dimers and TPA is reversibly oxidized. Interestingly, DFT calculations suggest that steric hindrance and electrostatic interactions dominate the radical cation reactivity. Abstract : Push‐pull networks : Arylamine derivatives constitute outstanding building blocks for the preparation of electroactive materials for opto‐electronic applications. Here, we study and rationalize the electrochemical dimerization tendencies of two D‐π‐A push‐pull molecules based on arylamine donor groups through spectroelectrochemistry and theoretical calculations. The electrochemical behavior of one of the two push‐pull molecules is exploited in its tetrameric counterpart to generate 3D push‐pull networks upon electropolymerization.